Mitochondrial hepatopathies: Advances in genetics and pathogenesis - Lee, Way Seah; Sokol, Ronald J. (Wiley, 2013)
Hepatic involvement is a common feature in childhood mitochondrial hepatopathies, particularly in the neonatal period. Respiratory chain disorders may present as neonatal acute liver failure, hepatic steatohepatitis, cholestasis, or cirrhosis with chronic liver failure of insidious onset. In recent years, specific molecular defects (mutations in nuclear genes such as SCO1, BCS1L, POLG, DGUOK, and MPV17 and the deletion or rearrangement of mitochondrial DNA) have been identified, with the promise of genetic and prenatal diagnosis. The current treatment of mitochondrial hepatopathies is largely ineffective, and the prognosis is generally poor. The role of liver transplantation in patients with liver failure remains poorly defined because of the systemic nature of the disease, which does not respond to transplantation. Prospective, longitudinal, multicentered studies will be needed to address the gaps in our knowledge in these rare liver diseases. (HEPATOLOGY 2007;45:1555–1565.)